Effect of amniotic membrane transplantation on corneal healing and proteoglycan expression in an experimental model of limbal deficiency in rabbits - Andrade, Alexandre Lima de [UNESP]; Campos, Mauro Q.; Gomes, Jose A. P.; Berto, Alessandra G. A.; Michelacci, Yara M. (Wichtig Editore, 2010)
PURPOSE. Amniotic membrane transplantation (AMT) has been used as a graft or as a dressing in ocular surface reconstruction, facilitating epithelization, maintaining normal epithelial phenotype, and reducing inflammation, vascularization, and scarring. The corneal transparency is due, at least in part, to the arrangement in orthogonal lamellae of collagen fibrils, surrounded by proteoglycans (PGs). These PGs regulate fibrilogenesis, the matrix assembly, and ultimately the corneal transparency. The purpose of the present study was to investigate the effects of AMT upon the corneal PGs after severe limbal injury.METHODS. Experiments were performed on the right corneas of 22 New Zealand female albino rabbits, and their left corneas were used as matched controls. These animals were divided into 3 groups: G1 (n = 10): total peritomy and keratolimbectomy, followed by application of 0.5 M NaOH; G2 (n = 10): submitted to the same trauma as G1, and treated by AMT; G3: no trauma, only AMT (n = 2). The right corneas of G2 and G3 were covered by DMSO 4 cryopreserved human amniotic membrane, fixed by interrupted 9-0 mononylon sutures, with its stromal face toward the ocular surface. After 7 or 30 days, the corneas were removed and PGs were extracted.RESULTS. Normal corneas contained approximately 9 mg of PGs per gram of dry tissue. AMT on intact cornea (G3) did not cause any changes in the concentration of PGs. In contrast, injured corneas contained much less PGs, both on the seventh and on the 30th day posttrauma. The PG concentration was even lower in injured corneas treated by AMT. This decrease was due almost exclusively to dermatan sulfate PGs, and the structure of dermatan sulfate was also modified, indicating changes in the biosynthesis patterns.CONCLUSIONS. Although beneficial effects have been observed on clinical observation and concentration of soluble proteins after AMT, the normal PG composition of cornea was not attained, even 30 days postinjury, indicating that the normal ocular surface reconstruction, if possible, is a long-term process. (Eur J Ophthalmol 2010; 20: 290-9)
Keywords: Cornea; Glycosaminoglycan; Human amniotic membrane; Proteoglycan; Rabbit